Voci dall’Inferno: Dante per esprimere l’indicibile - Elvira Mercatanti; Angelo Mario Del Grosso; Marina Riccucci (Umanistica Digitale)
Voci dall'Inferno is a research project of the University of Pisa, directed by Professor Marina Riccucci (University of Pisa) since 2016, with the support of Dr. Angelo Mario Del Grosso (CNR-ILC, Pisa). The project has two principal objectives: a) digitizing and encoding through XML-TEI the first digital corpus of non-literary testimonies that survived the concentration camps, including written and oral sources; b) identifying, quantifying, and evaluating the presence of Dante's lexicon and allusions within these testimonies. The research is based on the assumption that many survivors, regardless of their background, adopted Dante's lexicon, particularly from the Inferno of the Divine Comedy, to express the experiences of the Lager. The project focuses on non-literary testimonies, a textual typology through which those who lived the Lager describe their experiences in different forms ranging from oral (audio and video sources) to written (diaries, letters, memoirs). Each typology has structural, functional and semantic differences that must be identified and appropriately represented during the encoding process. The construction of the digital corpus makes it possible firstly to collect, encode and preserve non-literary testimonies, and secondly to use computational tools and methods to study, analyse and deepen these sources. The Voci dall’Inferno Web application allows to catalog, exploit, analyse and query all the available testimonies. Among the main functionalities, the application provides users to read each encoded testimony and to access statistics about the phenomena characterizing the primary source, which were extracted during the encoding phase. The application also makes it possible to highlight the presence of Dante's lexicon both within individual testimonies and across the entire corpus. Part of the paper illustrates the results of the work carried out by Elvira Mercatanti for her Master's Thesis in Humanistic Informatics.